Perpetrator effects of ciclosporin (P-glycoprotein inhibitor) and its combination with fluconazole (CYP3A inhibitor) on the pharmacokinetics of rivaroxaban in healthy volunteers - Brings, Antonia; Lehmann, Marie-Louise; Foerster, Kathrin; Burhenne, Jürgen; Weiß, Johanna; Haefeli, Walter E.; Czock, David (British journal of clinical pharmacology, 2019)
AIMS: Rivaroxaban exposure is considerably increased by drugs that are combined P-glycoprotein (P-gp) and strong cytochrome P450 (CYP) 3A inhibitors (e.g. ketoconazole). The aim of the present study was to investigate the effects of the potent P-gp inhibitor ciclosporin and its combination with the moderate CYP3A inhibitor fluconazole on rivaroxaban pharmacokinetics and on CYP3A activity. - METHODS: Twelve healthy volunteers received 20 mg rivaroxaban orally alone, in combination with ciclosporin (dose-individualized oral regimen), and in combination with ciclosporin and fluconazole (400 mg day-1 orally). CYP3A4 activity was estimated using a midazolam microdose. Pharmacokinetics was analysed using noncompartmental and compartmental methods. - RESULTS: Compared to baseline, ciclosporin increased rivaroxaban average exposure by 47% (90% confidence interval 28-68%), maximum concentration by 104% (70-146%), and decreased CYP3A4 activity by 34% (25-42%). Ciclosporin combined with fluconazole increased rivaroxaban average exposure by 86% (58-119%) and maximum concentration by 115% (83-153%), which was considerably stronger than observed in historical controls receiving rivaroxaban with fluconazole alone, and decreased CYP3A4 activity by 79% (76-82%). - CONCLUSION: Patients treated with rivaroxaban in combination with single modulators of multiple elimination pathways or multiple modulators of single elimination pathways (CYP3A, P-gp) require particular care.
Gesehen am 25.07.2019